The Discovery of a Palladium(II)‐Initiated Borono‐Catellani Reaction - Chen, Shuqing; Liu, Ze‐Shui; Yang, Tao; Hua, Yu; Zhou, Zhiyu; Cheng, Hong‐Gang; Zhou, Qianghui (Angewandte Chemie International Edition, 2018)
Reported is a novel palladium(II)‐initiated Catellani‐type reaction that utilizes widely accessible aryl boronic acids as the substrates instead of aryl halides, thereby greatly expanding the existing scope of this powerful transformation. This borono‐Catellani reaction was promoted by cooperative catalysis between Pd(OAc)2 and the inexpensive 5‐norbornene‐2‐carbonitrile. Practicality is the striking feature of the reaction: it is run open to air at ambient temperature and no phosphine ligand is needed. This mild, chemoselective, and scalable protocol is compatible with a large range of readily available functionalized aryl boronic acids and bromides, as well as terminating olefins (50 examples, 39–97 % yields). Moreover, the orthogonal reactivity between the borono‐Catellani and classical Catellani reaction was demonstrated. This work is expected to open new avenues for developing novel Catellani‐type reactions. Put a B on it: A PdII‐initiated borono‐Catellani reaction using readily available aryl boronic acids as the substrates, instead of aryl halides, was developed. The reaction is promoted by Pd(OAc)2 and 5‐norbornene‐2‐carbonitrile, and is run open to air at ambient temperature without a phosphine ligand. This chemoselective protocol is compatible with a range of functionalized aryl boronic acids and bromides, as well as terminating olefins.